Protocolos de bioseguridad y satisfacción del cliente en el Hotel Europa, 2021 - Perez Garcia, Wilfredo Junior (2023)
The objective of this thesis is to determine the relationship between the biosafety protocol and customer satisfaction at the Hotel Europa, 2021, I chose to be of an applied type, correlational descriptive level and non-experimental design, the population was made up of 65 guests of said hotel, for data collection the survey was used as a technique and the questionnaire as an instrument. Well, in the results it was determined that the biosecurity protocol has been applied regularly (29%), this is because sometimes the salon service is for the exclusive use of guests, in addition, the company sometimes opts for the services digital to avoid contact with them as much as possible. On the other hand, customer satisfaction is average (28%) since the modern facilities are more than expected and the security within the hotel is the same as expected. In conclusion, there is a significant relationship between sanitary surveillance and customer satisfaction corroborated by a considerable positive value and significance (r=0.712; p= 0.000).